Reflectance Confocal Microscopy and Dermoscopy For the Diagnosis and Treatment of Cutaneous Larva Migrans - Tang N; Huang QA; Cai LH; Deng DM; Niu M (Clinical, Cosmetic and Investigational Dermatology, 2023)
Nan Tang,1,* Qing-An Huang,2,* Lan-Hua Cai,1 Dong-Mei Deng,3 Mu Niu4 1Departments of Traditional Chinese Medicine, Guangzhou Red Cross Hospital of Jinan University, Guangzhou, Guangdong, People’s Republic of China; 2Department of General Ward, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China; 3Health Management Center, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China; 4Department of Cosmetic Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mu Niu, Department of Cosmetic Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, People’s Republic of China, Email 382219948@qq.com Dong-Mei Deng, Health Management Center, The Fifth People’s Hospital of Hainan Province, Haikou, People’s Republic of China, Email m15289975100@163.comAbstract: We describe a 39-year-old woman with a 1-month-old linear erythema diagnosed with cutaneous larva migrans by reflectance confocal microscopy (RCM). This case reveals that the great significance of diagnosing and treating cutaneous larva migrans (CLM) by RCM and dermoscopy, which might provide novel insights into dermatological clinical practice.Keywords: reflectance confocal microscopy, cutaneous larva migrans, linear erythema